Exploring Teaching Strategies for Work-based Learning in TVET Practices: A Qualitative Study - Rohanai, Reyanhealme; Othman, Hasyamuddin; Paimin, Aini Nazura; Ismail, Affero; Razali, Siti Solehah (Journal of Technical Education and Training, 2024)
Work-based learning (WBL) has been acknowledged as one of powerful learning strategy that empowers students learning experiences through real working exposure. However, there still exists issues in the lack of teaching delivery to cope up with students learning expectation in the industry and thus affect in achieving student learning objectives. This issue has lead to the needs of compelling opportunity for enhancement, particularly concerning WBL teaching strategies. Tailoring specific methodologies in Work Based Learning(WBL) instruction has the potential to significantly enrich students' learning journeys. Consequently, this study endeavors to delve into the realm of WBL practices within the TVET landscape, focusing on the exploration of pivotal teaching elements through the lens of experiential learning approaches. A qualitative analysis involving thematic analysis has been used to process data gathered from semi-structured interview with seven (7) academic experts. As to provide insights for mentioned issue, this study revealed a comprehensive active learning activities to be applied with experiential learning instructional delivery in Work Based Learning (WBL) teaching setup. The implementation of case study, problem-based, and inquiry-based learning activities promotes direct engagement to real working experiences. Whereby, discussion and logbook reporting activities are recommended to facilitate reflective observation by instructors. Inquiry-based or industrial documentation analysis activities can aid in conceptualizing students' understanding of their learning experiences. For meaningful practical application, conducting project executions or competency tests is advised to encourage students to apply their learned experiences in various industrial contexts. It is advisable that future research could study the application of this teaching strategy in WBL practices which lead to more informed guidelines to design practical hands-on activities that most appropriate for learners’ background and expectations.